2008
DOI: 10.1002/art.23594
|View full text |Cite
|
Sign up to set email alerts
|

(−)‐Epigallocatechin‐3‐gallate suppresses osteoclast differentiation and ameliorates experimental arthritis in mice

Abstract: Objective. To verify the effects of (-)-epigallocatechin-3-gallate (EGCG) on osteoclast differentiation and on experimental arthritis in mice.Methods. Human osteoclasts were differentiated from peripheral blood monocytes. The effects of EGCG were examined by tartrate-resistant acid phosphatase ( Conclusion. EGCG suppressed osteoclast differentiation and ameliorated experimental arthritis in mice over the short term. It remains to be established whether EGCG is useful for the prevention and treatment of osteopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 39 publications
3
69
0
Order By: Relevance
“…1,5 Additionally, EGCG was found to induce apoptotic cell death of osteoclast-like multinucleated cells 6,7 and ameliorated experimentally induced arthritis in mice. 8 Such pharmacological effects of catechins may be useful for prophylaxis or treatment of inflammatory bone disease. Recent in vitro studies show that EGCG increases bone mineral nodules in cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 Additionally, EGCG was found to induce apoptotic cell death of osteoclast-like multinucleated cells 6,7 and ameliorated experimentally induced arthritis in mice. 8 Such pharmacological effects of catechins may be useful for prophylaxis or treatment of inflammatory bone disease. Recent in vitro studies show that EGCG increases bone mineral nodules in cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Older women who drank tea exhibited higher BMD measurements than did women who did not drink tea (7). Tea polyphenols may be primarily responsible for the health benefits associated with tea; (−)-epigallocatechin-3-gallate (EGCG), a tea polyphenol, suppressed osteoclast differentiation and ameliorated RA in a mouse model of the disease (8).…”
Section: Introductionmentioning
confidence: 99%
“…The data obtained showed a significant correlation between the decrease in the levels of CRP, ESR, Rf, IL-6 and TNF-α in good and moderate green tea RA responders as compared to nonresponders, whereas the disease activity remained unchanged. These results demonstrated the antirheumatic activity of green tea which may be related to the antioxidant and anti-inflammatory of its phenolic compounds, especially catechins (Morinobu et al, 2008;Lin et al, 2008). Also, many studies reported that treatment of green tea reduced oxidative stress free radicals induced production of proinflammatory cytokines TNF-α, IL-6, CRP and NF-kB activation in a dose dependent manner (Kim et al, 2000;Wahyudi and Sargowo, 2007;Ramesh et al, 2009).…”
Section: Discussionmentioning
confidence: 74%